FORMULATION AND EVALUATION OF SEMISYNTHETIC ANTIFUNGAL INSITU GEL CONTAINING SENNA AURICULATA AND AZADIRACHTA INDICA LEAVES - Gawade Sangram Santosh; Ingale Gauri Raosaheb; Pachpute Madhuri Rajendra; Gunjal Sujit Sakharam; Sake Vaishnavi Sanjay; Dr. Veer Sujata Umakant; Dr. Khedkar Amol Navnath (The Bioscan, 2026)
The antimicrobial in-situ gel containing extracts of Senna auriculata flower and Azadirachta indica leaves for topical drug delivery. Herbal medicines are widely used for the treatment of skin infections and inflammatory conditions due to their therapeutic effectiveness, safety, easy availability. The prepared formulations were evaluated for various physicochemical parameters including appearance, color, odor, homogeneity, pH, viscosity, spread ability, gelation capacity. Spread ability was determined to evaluate ease of application, while viscosity studies were performed using Brookfield viscometer to determine rheological behavior of the gel. The pH of the formulation was maintained within the range suitable for skin application. The antimicrobial activity of the prepared in-situ gel was evaluated by agar well diffusion method against selected microorganisms including Staphylococcus aureus, Escherichia coli, and Candida albicans. The optimized formulation exhibited significant antimicrobial activity with satisfactory zone of inhibition against test organisms. Stability studies were carried out under different storage conditions to evaluate physical stability, pH, viscosity, and homogeneity of the formulation. The results of the study demonstrated that the formulated in-situ gel showed satisfactory physicochemical characteristics, good spread ability, and acceptable viscosity, excellent and significant antimicrobial activity.